Designing an Operational Knowledge and Information Sharing System : The Malawi Social Action Fund - Khan, Aisha Rahaman (World Bank, Washington, DC, 2012)
The Malawi Social Action Fund (MASAF) has been in operation since July 1995 and was established specifically to directly finance communities to implement demand-driven sub-projects. Recently, (2004) under MASAF 3 it has begun the process of establishing a Knowledge and Information Sharing System (KISS) that will facilitate knowledge documentation and dissemination in order to improve the quality of project and program delivery. This system seeks to build on and integrate the experiences and lessons accumulated in the last nine years and move towards making MASAF a knowledge sharing and learning organization.